1994
DOI: 10.1111/j.1469-8137.1994.tb02997.x
|View full text |Cite
|
Sign up to set email alerts
|

Ozone effects on nitrogen incorporation and superoxide dismutase activity in spruce seedlings (Picea abies L.)

Abstract: SUMMARYThe influence of low concentrations of ozone (100 ppb) on nitrogen incorporation and the specific activity of superoxide dismutase (SOD) in 3-yr-oId cloned spruce seedlings was studied under controlled conditions (potted plants in fumigation chambers). For the determination of nitrogen uptake, '''^N tracer experiments were performed using emission spectrometric isotope analysis. Superoxide dismutase (SOD) activity was determined by inhibition of formazan formation.Low doses of ozone led to a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…With enhanced ozone, nitrogen concentrations in shoots of Pinus halepensis seedlings increase compared to the roots (Kytöviita et al, 2001) and N allocation is influenced in poplar cuttings under ozone fumigation by changing plant growth (Bielenberg et al, 2002). Jung et al (1994) showed a significant increase of NO 3 uptake from the soil in Picea abies seedlings after ozone fumigation. In the present study, total N in fine roots, but not in leaves, was decreased under 2 × O 3 (Fig.…”
Section: Ozone Fumigation Affected Fine Root Total Nmentioning
confidence: 96%
“…With enhanced ozone, nitrogen concentrations in shoots of Pinus halepensis seedlings increase compared to the roots (Kytöviita et al, 2001) and N allocation is influenced in poplar cuttings under ozone fumigation by changing plant growth (Bielenberg et al, 2002). Jung et al (1994) showed a significant increase of NO 3 uptake from the soil in Picea abies seedlings after ozone fumigation. In the present study, total N in fine roots, but not in leaves, was decreased under 2 × O 3 (Fig.…”
Section: Ozone Fumigation Affected Fine Root Total Nmentioning
confidence: 96%
“…22 The effect of the different levels of arsenic contamination on the plant metabolism was examined by means of the 15 N-tracer technique. [23][24][25][26] In plant cells, nitrogen plays an important role as a main component of amino acids, proteins and other biomolecules. Therefore, nitrogen metabolism, including the uptake and assimilation of nitrate, is one basis for an optimal biosynthesis of amino acids and proteins, which are involved in nearly all processes in plants.…”
Section: Introductionmentioning
confidence: 99%